Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1128/aac.00528-16
|View full text |Cite
|
Sign up to set email alerts
|

Nonprescription Antimicrobial Use in a Primary Care Population in the United States

Abstract: c Community antimicrobial resistance rates are high in communities with frequent use of nonprescription antibiotics. Studies addressing nonprescription antibiotic use in the United States have been restricted to Latin American immigrants. We estimated the prevalence of nonprescription antibiotic use in the previous 12 months as well as intended use (intention to use antibiotics without a prescription) and storage of antibiotics and examined patient characteristics associated with nonprescription use in a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 21 publications
5
52
2
1
Order By: Relevance
“…5 Zoorob et al, in a study conducted in the USA observed that 14.2% of the respondent reported that they have antibiotics at their home. 6 An Iranian household survey reported that antibiotics were found in 9.8% of homes. 7 In our study, the most common point of origin for the unused antibiotics were public hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5 Zoorob et al, in a study conducted in the USA observed that 14.2% of the respondent reported that they have antibiotics at their home. 6 An Iranian household survey reported that antibiotics were found in 9.8% of homes. 7 In our study, the most common point of origin for the unused antibiotics were public hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…A study on unprescribed antibiotics usage in the USA also reported that about 74.0% of the respondents used leftover antibiotics. 6 A household survey conducted in Iran reported that 9.8% of homes had unused antibiotics left-overs from doctors' prescriptions. 7 We observed that most common health conditions for which the unused antibiotics were originally procured was the respiratory tract infection, followed by diarrhoea, followed by fever.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations